A study to assess the knowledge and perception of innovative teaching and evaluation methods in nursing education - Dawri, Ashalata; J, Vaishali; B, Dhanraj; G, Santhosh; S, Arunima (International Journal of Nursing Research, 2023)
Nursing globally transforming from conventioneer to contemporary practice in 21st century, involves utilization of technology for, information, communication, and mass media thereby has bringing out the world more closer world-wide. The consumers demand high-quality nursing services. The skilled competent qualified nurse practitioners need to be prepared in order to provide care services. Thus the nursing school/colleges plays significant role in preparation of qualified nurses. The study is planned to assess the knowledge of innovative teaching and evaluation methods and views of the faculty to keep pace, update themselves in relation to this changing scenario of nursing education and practice. The study revealed that there is a significant difference between pre-test and post-test value in the level of knowledge regarding ICT, innovative teaching methods and evaluation technique among the nursing teachers. Therefore the knowledge plays a vital role among nursing teachers and it is significant at 5 percent. Ninety-six percentages of teachers agree that there is need of modification in current methods of teaching and evaluation. It also emphasizes the availability and use of information communication technology in nursing education institutions is essential so as to move on par with general education stream.